Respuesta :
[tex]\huge\color{pink}\boxed{\colorbox{Black}{♔︎Answer♔︎}}[/tex]
349525
Step-by-step explanation:
[tex] = \textsf{\underline{\large{To find :-}}}[/tex]
The sum of first 10 terms
[tex] \textsf{\underline{\large{Given :-}}}[/tex]
a = 1
r = 4
[tex]\sf{ \huge{ \underline{ \underline {Solution :-}}}}[/tex]
[tex] \sf S_n = \frac{a( {r}^{n} - 1)}{(r - 1)} ,if \: r ≠ 1[/tex]
here n = 10
we just need to substitute the value
[tex] \sf \implies S_{10} = \frac{1( {4}^{10} - 1) }{(4 - 1)} \\ \\ \sf \implies S_{10} = \frac{ {4}^{10} - 1 }{3} \\ \\ \sf \implies S_{10} = \frac{1048576 - 1}{3} \\ \\ \sf \implies S_{10} = \frac{1048575}{3} \\ \\ \sf { \red{ \implies S_{10} = 349525}}[/tex]
Answer:
349525
Step-by-step explanation:
Sum of a Geometric Sequence
- Sₙ = a(rⁿ - 1) / (r - 1)
Taking :
- a = 1
- r = 4
- n = 10
Solving
- S₁₀ = 1(4¹⁰ - 1) / 4 - 1
- S₁₀ = 1048576 - 1 / 3
- S₁₀ = 1048575/3
- S₁₀ = 349525